2018
DOI: 10.1007/s11910-018-0903-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Sleep Disturbances in Myotonic Dystrophy Types 1 and 2

Abstract: Purpose of Review To update current knowledge regarding sleep disturbances and myotonic dystrophies so as to better understand if sleep symptoms may help in the early recognition of the two genetic subtypes: myotonic dystrophy type 1 (DM1) and myotonic dystrophy type 2 (DM2). Recent Findings Sleep-disordered breathing (SDB), restless legs syndrome, periodic limb movements in sleep, hypersomnia, and REM sleep dysregulation are frequently described in DM1 patients. SDB does not always explain hypersomnia, but a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 92 publications
0
3
0
1
Order By: Relevance
“…The simultaneous onset of RLS and PPS symptoms (91) and the positive response to pramipexole in an uncontrolled trial by Kumru et al (93) have been interpreted as a pathophysiological link between RLS and PPS (98). The putative link between RLS and neuroimmunological alterations (100, 101) may also suggest shared pathophysiological processes between PPS and RLS (99). Furthermore, a higher incidence of cauda equina syndrome (102) and renal impairment (103) has also been reported in PPS but the association between these syndromes remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…The simultaneous onset of RLS and PPS symptoms (91) and the positive response to pramipexole in an uncontrolled trial by Kumru et al (93) have been interpreted as a pathophysiological link between RLS and PPS (98). The putative link between RLS and neuroimmunological alterations (100, 101) may also suggest shared pathophysiological processes between PPS and RLS (99). Furthermore, a higher incidence of cauda equina syndrome (102) and renal impairment (103) has also been reported in PPS but the association between these syndromes remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…myotonic dystrophy (DM) [27] and Friedreich's ataxia (FA) [28]), and whether sleep disturbances are also related to the trinucleotide repeat length in these diseases. Previous studies found hypersomnia, increased periodic limb movements in sleep (PLMS), sleep apnea, SWS, and REM sleep duration, and decreased N2 in DM1 patients [29,30]; whereas decreased TST, SE, percentage of SWS and REM sleep, and increased WASO were found in DM2 patients [31]. To our knowledge, how PSG changes in FA patients compare with controls has not been established; however, the presence of sleep apnea correlates with the duration and clinical severity of FA [32].…”
Section: Moderator Analysismentioning
confidence: 94%
“…Alvászavarok gyakran fordulnak elő szinte valamennyi neuromuscularis betegség esetén, ezért jelentős szerepet játszanak a betegek életminőségének romlásában. A leggyakoribb alvászavarok DM1-ben: alvásfüggő légzészavar (SDB), hypersomnia és nyugtalanláb-szindróma [11]. Alvásvizsgálatok alapján az obstruktív alvási apnoe (OSAS) előfordulása 69% volt DM1-és 42% DM2-betegek között; az összes beteg 28%-ánál volt szükség nem invazív lélegeztetés (NIV) bevezetésére [12].…”
Section: Alvásfüggő Légzészavarunclassified